DISTRIBUTION OF PHOSPHOLIPID MEMBRANES AND ACTIVITY OF APOPTOTIC ENZYMES IN TYPE 2 DM - Negmatova, Gulzoda Shukhratovna; Mansurova, Gulsum Zaydinovna; Rustamova, Malika Sirojiddin qizi; Abdiyev , Lazizbek Sobir oʻgʻli (Educational Research in Universal Sciences, 2024)
Chronic hyperglycemia changes the composition of erythrocyte membranes, but the mechanisms of damage and activation of apoptosis are not well understood. A common feature of membranes in all eukaryotic cells is the non-random distribution of lipids across the bilayer. Lipid asymmetry in membranes is a consequence of multiple factors, including the biophysical properties of lipids that dictate their ability to spontaneously “flip” their polar headgroups through the hydrophobic membrane interior, and the presence of transporters (enzymes) that assist in active lipid translocation across the bilayer.